Keterkaitan Tipologi dengan Fungsi dan Bentuk: Studi Kasus Bangunan Masjid - Suharjanto, Gatot (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Besides having a particular function or purpose, a building also has certain characters that generally appear and are accumulated into an image or impression given by anyone who sees the building. Function is a fundamental starting point for all architectural expression. The influence of function on the architecture is quiteobvious especially when we observe differences in the use of certain building and how certain activities can create the form of the building. However, is it true that the function and form of the building has any relation with the formation of building classification (typology)? For that reason, this paper discusses a case study ofmosque buildings.